Radiation characteristics of Vivaldi antenna on the surface of the wedge-cylinder adjunction - Yukhanov, Yu. V.; Gevorkyan, A. V.; Tyu, Privalova (2016 IEEE 5th Asia-Pacific Conference on Antennas and Propagation (APCAP), 2016)
This paper presents an analysis of the directional properties of antipodal Vivaldi antenna located on the faces of the wedge, coupled with the cylinder. Two variants of the implementation of the antennas were studied. In the first case one antenna is located on each side of the wedge symmetrically to the edge, in the second one there are two antennas. Comparative analysis of these antennas is made. The influence of value of the angle at vertex of the wedge and its sizes on antenna parameters is investigated. The frequency characteristics and the directional properties of the antennas depending on their structural dimensions and location were considered.